Low frequency repetitive transcranial magnetic stimulation promotes plasticity of the visual cortex in adult amblyopic rats - Zheng, Jing; Zhang, Wenqiu; Liu, Longqian; Hung Yap, Maurice Keng (Frontiers in Neuroscience, 2023)
The decline of visual plasticity restricts the recovery of visual functions in adult amblyopia. Repetitive transcranial magnetic stimulation (rTMS) has been shown to be effective in treating adult amblyopia. However, the underlying mechanisms of rTMS on visual cortex plasticity remain unclear. In current study, we found that low-frequency rTMS reinstated the amplitude of visual evoked potentials, but didn’t influence the impaired depth perception of amblyopic rats. Furthermore, the expression of synaptic plasticity genes and the number of dendritic spines were significantly higher in amblyopic rats which received rTMS when compared with amblyopic rats which received sham stimulation, with greatly reduced level of inhibition and perineuronal nets in visual cortex, as observed via molecular and histological investigations. In conclusion, the results provide further evidence that rTMS enhances functional recovery and visual plasticity in an adult amblyopic animal model.